Braise : a journey through international cuisine - Boulud, Daniel; Clark, Melissa (New York, USA : ECCO, 2006)
Chef Daniel Boulud's definitive cookbook on the time-honored technique of braising. Braising is "moist heat" cooking, where a small amount of liquid is cooked along with the food in a closed container over long periods of time. A successful braise mingles the flavors of the food being cooked with the liquid it is cooked in, and, because the cooking takes place slowly without burning the food, the technique results in rich, aromatic flavors. Featuring dishes from Thailand, Italy, Mexico, Turkey, Lebanon, France, Russia, China and many other places, this is a comprehensive guide to braising, for cooks of every skill level.--From publisher description.
Meat -- Poultry and rabbit -- Fish and seafood -- Vegetables and beans -- Fruit and other desserts.
Includes index.
CBA
Text in English
Keywords: Braising (Cooking); International cooking; Cookbooks